Economic Adjustment and Income Adequacy of Malay Female-Headed Households in Malaysia - Yagoub, Fawzia (2005)
The main purpose of this study was to investigate the economic adjustments and income adequacy of Malay female-headed households (FHHs) in Malaysia. The study attempted to answer the following six research questions; what are the economic resources, sources of income and economic adjustments before and after the women becoming FHHs, and what are the factors significantly influence the economic status, objective and subjective income adequacy of FHHs? Secondary data collected among female headed households for the study entitled female headed household within the context of poverty carry out in 1994195 was used in this research. The data was analyzed using Statistical Package of Social Science (SPSS). The procedures used were descriptive statistics, t-tests, multiple regression and multiple discriminant analysis. The data analysis indicated that FHHs had access to limited economic resources. One of the main economic adjustments undertaken by the women was getting involved in employment to support their living. Three models explaining the economic status, objective and subjective income adequacy for widows, divorcees and all FHHs were tested in this research. Divorcee's economic status was significantly explained by education, income earned from employment, and ownership of properties while widow's economic status was significantly explained by ownership of properties, and other sources of income. Training, education, and income earned from employment contributed significantly to discriminate the divorcee's objective income adequacy. For widows it was found that income earned from other sources, employment, and remittance from children contributed significantly to discriminate the widow's objective income adequacy. Among FHHs there were only 34.2% divorcees and 27.9% widows whose income was adequate. When subjective income adequacy was analyzed there were 13% divorcees and 14.8% widows who perceived that their income is adequate. After taking into account all sources of income, majority of FHHs in this study; widows or divorcees were poor. Their low level of educational attainment and lack of skills contributed to such situation. Improve education and skills can be one of the strategies to help FHHs cope with the changing status from being intact family to female headed. To enhance the economic status of FHHs and reduce the incidences of poverty, relevant policies and more integrated programs should be formulated targeted FHHs. Addressing the needs of female headed households can be one of the effective strategies to sustain the low level of poverty in Malaysia.